Desiccation of the Extreme Thermoacidophile Metallosphaera sedula Grown on Terrestrial and Extraterrestrial Materials - Kölbl, Denise; Blazevic, Amir; Albu, Mihaela; Fasching, Christoph; Milojevic, Tetyana (Frontiers in Astronomy and Space Sciences, 2020)
Prokaryotes are among the most versatile organisms on Earth and their ability to adsorb metals for nutrient, energy or protection purposes can be noted in many different environments on our planet. The extreme thermoacidophilic archaeon Metallosphaera sedula is a metal-mobilizing archaeon capable of redox transformations during chemolithoautotrophic growth on diverse metal-bearing compounds. Examining the interfaces of this extreme metallophilic archaeon with various metal-bearing substrates of terrestrial and extraterrestrial origin, we have detected its selective preservation after desiccation. Cultivated on specific metal-bearing materials, e.g., tungsten-bearing scheelite, tungsten-bearing polyoxometalate, multimetallic waste products, and the NWA 1172 meteorite, cells of M. sedula can be preserved after dehydration, and therefore can potentially serve as a microbial fingerprint of the presence and/or activity of metal-transforming microorganisms. Preservation of desiccated M. sedula cells reported in this study has a discriminatory character, depending on the content and nature of the metal-containing compound used for cultivation of this metallophilic microorganism. The achieved preservation of dehydrated M. sedula cells facilitates our survivability studies with this desiccated microorganism during future space exposure experiments and under simulated space environmental conditions.